2004
DOI: 10.1097/01.asn.0000102475.94185.54
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Levels and Erythropoietin Doses in Hemodialysis and Peritoneal Dialysis Patients in the United States

Abstract: Abstract. Erythropoietic agents, a cornerstone of management, are a major component of the cost of renal replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 23 publications
2
37
1
6
Order By: Relevance
“…First, data on dialysis adequacy, residual renal function, delivered dialysis dose, anemia management, and mineral metabolism parameters were not available. However, previous studies suggested that PD patients tend to have higher residual renal function over time (9,32), similar target hemoglobins (33), and inconsistent differences in nutritional parameters (17,34). These differences should bias toward the null hypothesis or toward improved outcomes in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, data on dialysis adequacy, residual renal function, delivered dialysis dose, anemia management, and mineral metabolism parameters were not available. However, previous studies suggested that PD patients tend to have higher residual renal function over time (9,32), similar target hemoglobins (33), and inconsistent differences in nutritional parameters (17,34). These differences should bias toward the null hypothesis or toward improved outcomes in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, only 25% of patients who started PD treatment between 1995 and 2000 were treated with ESAs in the first 12 months (10). In addition, the achieved hemoglobin in recent years is significantly higher than that in the 1990s (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the achieved hemoglobin in recent years is significantly higher than that in the 1990s (11). Third, ESAs are administered subcutaneously in PD patients in contrast to intravenous administration in hemodialysis patients, and hence, doses are lower (10). Fourth, ESA administration and achieved hemoglobin are substantially more dependent upon patient adherence for PD patients than among those treated with hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Despite this, patients receiving peritoneal dialysis appear to require substantially lower doses of erythropoietin to control their anemia. 16,17 Possible reasons for this reduced epoetin dose requirement include a lower level of blood loss and inflammation in patients receiving peritoneal dialysis, the use of the subcutaneous route, as is usually the case in a peritoneal dialysis population, as well as improved dialytic removal of inhibitors of erythropoiesis. 16 Of interest in the present study, the mean dose of epoetin δ was numerically lower than the dose epoetin patients were receiving before entering the study.…”
Section: Resultsmentioning
confidence: 99%
“…Hematologic parameters were assessed weekly and the primary efficacy endpoint was the mean hemoglobin level over weeks [12][13][14][15][16][17][18][19][20][21][22][23][24]. Secondary endpoints included the mean treatment dose, mean hematocrit, and percentage of hemoglobin measurements >10 g/dL and hematocrit measurements >30%.…”
Section: Endpoints and Analysismentioning
confidence: 99%